Electrochemical sensing of oxalic acid using silver nanoparticles loaded nitrogen-doped graphene oxide. (July 2022) - Zafar, Muhammad Adeel; Liu, Yang; Allende, Scarlett; Jacob, Mohan V
Abstract: The adverse effects of oxalic acid (OA) on human health linked with its excessive consumption necessitates an improved sensor. Here, we demonstrate an electrochemical sensor for oxalic acid detection based on silver nanoparticles (Ag-Nps) and nitrogen-doped graphene oxide (N-GO) nanocomposite. N-GO, which was synthesized using atmospheric pressure microwave plasma has been first time employed for electrochemical application. The nanocomposite formation was confirmed through scanning electron microscopy and EDS elemental analysis. The nanocomposite-based sensor showed a higher current response, good selectivity and stability which can be attributed to the synergistic-effect of Ag-Nps and N-GO. Amperometric responses were proportional to the concentration of OA between 10 and 300 μM, and the detection limit was 2 μM. Graphical abstract: Image, graphical abstract